MENINGKATKAN AKTIVITAS BELAJAR IPA BIOLOGI SISWA MENGGUNAKAN MODEL BERPIKIR INDUKTIF - Irwansah; Mahariyanti, Ermila (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2022)
This study aims to determine the learning activities of Science Biology Class VII A students at MTs. Darul Aminin NW Aikmual using the Inductive Thinking Model. This type of research is Classroom Action Research (CAR) with the data collection tool used were observation sheets of teacher and student activities. Based on the data analysis, the results obtained in the first cycle of meeting I, the teacher's activity score was 59.37% in the fairly active category. The action was continued until the second cycle. At the second meeting of cycle II, the teacher's activity score was 78.12% with the active category. Cycle I Meeting I students’ activity score was 47.05% with quite active category. The action was continued until the second cycle. At the second meeting of cycle II, the student activity score was 64.70% in the active category. From these results it can be concluded that action research was successful because it can increase students' biology learning activities using the Inductive Thinking Learning Model.